Anticorrosive Behavior of SiCxNyOz Film Formed by Non-Heat Assistance Plasma-Enhanced Chemical Vapor Deposition Using Monomethylsilane, Nitrogen and Argon Gases. (2nd January 2020) - Watanabe, Toru; Hori, Kenta; Habuka, Hitoshi
Abstract : A SiC x N y O z film was formed on an aluminum substrate without any heating assistance using monomethylsilane, nitrogen and argon gases at 10–30 Pa by the parallel plate plasma-enhanced chemical vapor deposition method. The obtained film did not have any considerable pinhole and crack, based on the evaluation using a concentrated hydrogen chloride aqueous solution. The anti-corrosive behavior of the obtained film was studied by means of chlorine trifluoride gas etching at the concentration of 100% at atmospheric pressure and at various temperatures. The etching rate increased with the increasing temperature and with the increasing nitrogen concentration in the film. The increase in the nitrogen concentration in the film enhanced the fluorine diffusion through the film during the etching. The anticorrosive behavior was determined to be adjustable by the nitrogen concentration contained in the film.